'FOR THE HONOUR OF GOD AND THE WEAL OF HIS MAJESTY'S REALM …': REFORMATION STORIES FROM DOCUMENTS IN THE NATIONAL ARCHIVES. Issue 1 (April 2019) - Gill, Sylvia
Abstract : The survey records of the Court of Augmentations (collectively referred to as the 'chantry certificates') provide invaluable evidence of the process of Dissolution, including details of property used to endow the chantries and the purposes for which it was intended. The survey carried out during the reign of Edward VI adds personal details of the priests who were employed to offer prayers for the founders. This article demonstrates the importance of these documents and related material, and their use to uncover more about the priests whose lives were disrupted by the Dissolution, and the endowments that supported their foundations as well as the officials and practices of the Court of Augmentations itself.